Bottling Up Trust: A Review of Blockchain Adoption in Wine Supply Chain Traceability - Gowher Majeed Parry; Ioannis Revolidis; Joshua Ellul; Gordon J. Pace (IEEE Access)
Though viticulture, wine production and distribution, involves processes mainly revolving around a single component/ingredient — grapes, it still faces the challenges of supply chain management. Supply chains require significant trust among stakeholders, and whilst for the most parts modern day supply chains ‘work’, it is when failures/mistakes occur that risks are high. Blockchain technology has emerged as a potential solution to confront supply chain-related traceability, transparency, and trust issues — of which extensive work has been done in applying it to wine sector. In this paper, we provide an overview of the technology and its capacity to bring about transformative changes to the viticulture supply chain. The current state of blockchain assimilation in the wine supply chain is presented, whilst highlighting the benefits and challenges associated with utilising blockchain within the wine industry-related supply chains. We pinpoint technological, legal, and adoption obstacles that must be overcome to ensure the successful integration of blockchain within the viticulture supply chain. Drawing on the state-of-the-art and industry practices, we propose directions to overcome hurdles — which may better support enhanced supply chain traceability, amplified transparency, and consumer trust, improved quality assurance and safeguarding against counterfeiting and fraud within the viticulture industry.